CRIMINAL PROPOSAL OF ENFORCED DISAPPERANCE OF PEOPLE AS CRIMINAL BEHAVIOR AGAINST HUMANITY FOR THE COSTA RICAN CRIMINAL LAW - Salgado Mejía, Rafael Andree (2019)
The purpose of this paper is to analyze how the crime against humanity is classified in the Criminal Code of Costa Rica, in order to determine whether the enforced disappearance as a crime against humanity is under international standards of the type penal. Likewise, it will be show that enforced disappearance cannot be classified as a crime and as a crime against humanity in a single criminal category. Although it is true, reference will be made to the principles, judgments and norms, the epistemological position to be used will be legal formalism because we will focus on national and international regulations. Finally, some suggestions will be made to classify enforced disappearance as a crime against humanity.   KEY WORDS: Penal Code of the Republic of Costa Rica, Crime against humanity; Human Rights; Enforced disappearance.